Harmonic variations in three-phase induction motors fed by PWM inverter with different stator coil pitches - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
A sinusoidal pulse-width modulation (SPWM) inverter feeding five different chorded three-phase induction motors were tested for low-order odd harmonic voltage component and efficiency at different loads. Total harmonic distortion (THD) due to 3rd, 5th, 9th, 11th and 13th harmonics were less in a motor with (1-7) 120 degrees coil pitch. Particular harmonic order for each coil pitch was suppressed and the increasing quantity of efficiency in a motor with (1-6)100 degrees coil pitch was increased by 4,92 %. The full pitch motor with (1-10) 180 degrees coil pitch has more harmonics than other motors.
Keywords: coil pitch; chording; harmonics; stator winding; VOLTAGE